The Identerest Nexus: Exploring Patani Secessionism - Rochdi Mohan Nazala (Department of International Relations, Universitas Brawijaya, 2025)
This paper analyses the strengthening of secessionism in the Thailand’s southern region of Patani during Thaksin’s period through the conceptual framework of “identerest” (identity and interest”). Indeed, local’s aspiration of secessionism in Patani had continued to be a headache for the central government under in Bangkok under Thaksin. Strategies had been diffused by Thailand’s authority, including through the implementation of strict security measures, yet all of them fails to reach the main objective as to diminish the Patani’s secessionist movements. Instead, the Bangkok’s counter-secessionism policies have worsened the human rights situation on the ground and, as a consequence, fueled the already strong demand to secede. With an argument that it is better to look at the struggle in Patani as a symbolic mixture of both identity and interest or “identerest”, this paper examines the nature of conflict in Patani. In so doing, it traces the process through which the secessionism idea has emerged among the indigenous population of Patani, describes the roles of local leaders in the establishment of secessionist movements, and assesses the impacts of the government’s counter-secession policies in the South end of Thailand in prolonging the dispute.